Consequences of Monetary Depreciation on Houhehot Spending in Kinshasa (R.D.Congo) 2015-2017 - Musima Mungie Eleuthère (Economit Journal: Scientific Journal of Accountancy, Management and Finance, 2023)
This work consisted in experimenting the theories on the currency whhile trying to work on the depreciation of congolese France vis-a-vis the foreign currency . This choice was moticated to enrich knowledge on the role that money play in the economy as heritage. And then try to apply social science theories and research methods in a specific context. It is a question of constituting a probability sample (simple random sample) of a set of household expenses for two periods. That of relative price stability on the market and that of the general increase in the exchange rate. After having established a correlation betwueen thèse two variables, we try to raise in percentage, of how muche the monetary depreciation influences the volume of expenditure of the househods. To do this, we will apply a paired sample test.